IT STRATEGY: A Present Business Need (International Journal of Engineering and Computer Science, 2017)
Information Technology (IT) is an important field of study in a number of areas, Due to the numerous advantages of IT, Organizations are trying to implement IT applications to support their businesses. Therefore, this research aims to provide a better and clearer understanding of IT Strategy within organization by reviewing and analyzing current IT literature. In this research, we have tried to propose an IT strategy template after the reviewing of literature. The proposed template of effective IT strategy is believed to provide organizations with a practical synopsis of the IT strategy, which will in turn assist them to be successful with IT institutionalization within these businesses.